Analisis Pengaruh Kepercayaan Dan Risiko Pengguna Dalam Niat Pembelian Online Di PT. XYZ Dengan Menggunakan UTAUT (Unified Theory Of Acceptance And Use Of Technology) - Muhammad Iqbal Rofi'i; Ari Kusyanti; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PT. XYZ is the e-commerce site in Indonesia which was founded by Hendrik Tio with his friends in 1993 with the name of PT. XYZ. Until now there are many complaints submitted by the number of products that are not in accordance with the number of existing stock, abuse of promotion, slow response in handling consumer problems, goods received not in accordance with the desired, the price is more expensive than other sites, the process of a long refund and others. This research, used Unified Theory of Acceptance and Use of Technology (UTAUT) model as the main model with the behavioral intention. Performance expectancy, effort expectancy, social influence, facilitating condition, perceived trust and perceived risk. The perceived trust variable was affected by perceived risk, perception market orientation, and perceived site quality. Samples obtained were 122, which based on Hair formula. Then the data analysis in this study using multiple linear regression. The results of this research indicate that the variable of perfomance expectancy, facilitating conditions, perceived trust and perceived risk affect significantly toward behavioral intention. Besides, the variables of perceived market orientation and perceived site quality affect significantly toward perceived trust.